Knowledge and experience of young people regarding drug misuse, 1969-94. - Wright, J. D. (BMJ Group, 1995)
OBJECTIVE--To monitor young people's knowledge and experience of illicit drugs between 1969 and 1994 at intervals of five years. DESIGN--The same anonymously completed questionnaire was used throughout. SETTING--Three Wolverhampton secondary schools representing three different socioeconomic groups. SUBJECTS--392 pupils aged 14 to 15 completed the questionnaire in 1994. Previous sample sizes were 471 in 1969, 523 in 1974, 648 in 1979, 540 in 1984, and 380 in 1989. MAIN OUTCOME MEASURES--Self reported levels of knowledge and experience of illicit drugs. RESULTS--Over 25 years the proportion of pupils who knew someone taking drugs more than quadrupled from 15% (71/471) to 65% (254/392), and the proportion who had been offered drugs increased ninefold from 5% (24) to 45% (175). Both of these proportions more than doubled over the past five years. In 1994 the proportions of pupils mentioning "ecstasy" (methylenedioxymethamphetamine), amphetamines, and crack cocaine increased significantly (P < 0.01) and the proportion mentioning opiates decreased significantly (P < 0.01). "Poppers" (amyl nitrite) were mentioned for the first time. "To feel big, to show off, look grown up" has continued to be the main perceived reason for taking drugs. Television has continued to be the main source of information. CONCLUSIONS--In the past five years in particular young people's exposure to illicit drugs has increased dramatically. Despite more education about drugs, pupil's knowledge remains limited. Social pressures remain the first perceived reason for taking drugs. The media have a responsibility not to glamorise drugs.